The Green Approach of Cerium Oxide Nanoparticle and Its Application for Photo-degradation of Phenol Dye - Gusliani Eka Putri; Syukri Arief; Ahmad Hafizullah Ritonga; Wiya Elsa Fitri; Eliza Arman; Arniat Christian Telaumbanu; Rahmi Novita Yusuf (Universitas Gadjah Mada, 2023)
The approach to the synthesis of cerium oxide nanoparticles (CeO2NPs) using plants as capping agents has been widely researched because of its eco-friendly, low-cost, simple, effective, and reusability. In this research, we used Moringa oleifera leaf extract-mediated CeO2NPs. CeO2NPs were characterized by XRD, FTIR, SEM, TEM, and DRS UV-vis. The photocatalytic activity of CeO2NPs was tested using a phenol dye concentration of 7 mg/L with variations in photocatalyst weight of 10, 20, 30, 40, 50, 60, 70, 80, 90, and 100 mg under UV irradiation, respectively, with time variations of 15, 30, 45, 60, 75, 90, 105, 120, 135, and 150 min. SEM and TEM morphology results showed that the CeO2NPs were spherical and agglomerated. The crystal structure is cubic, with a crystal size of 18 nm with a band gap of 2.87 eV. CeO2NPs showed high photo-degradation phenol dye of 94.45% under visible light in 120 min irradiation time. The results show that M. oleifera leaf extract could be as inexpensive and safe for synthesizing other metal oxide nanoparticles, potentially having applications in the biomedical and environmental fields.